2023
DOI: 10.1186/s12905-023-02231-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health of Syrian refugee women in Lebanon: a descriptive analysis of the Sijilli electronic health records database

Abstract: Background The Syrian conflict has been responsible for the highest exodus of refugees, with Lebanon hosting the greatest number of refugees per capita, which placed a significant strain on an already overburdened healthcare system. Women are the most vulnerable group in times of conflict and displacement, with sexual and reproductive health and rights often neglected. This study focuses on the obstetric characteristics and pregnancy outcomes of Syrian Refugee (SR) women in Lebanon, in Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…While there are several studies re ecting the state of maternal health in Lebanon (29,(33)(34)(35)(36), very few focus on recent health data of disadvantaged women, particularly in primary healthcare settings (37,38).…”
Section: Status Of Maternal Health Among Disadvantaged Populations In...mentioning
confidence: 99%
“…While there are several studies re ecting the state of maternal health in Lebanon (29,(33)(34)(35)(36), very few focus on recent health data of disadvantaged women, particularly in primary healthcare settings (37,38).…”
Section: Status Of Maternal Health Among Disadvantaged Populations In...mentioning
confidence: 99%
“…While there are several studies reflecting the state of maternal health in Lebanon [32,[36][37][38][39], very few focus on recent health data of disadvantaged women, particularly in primary healthcare settings [40,41].This gap in the availability of recent data may be attributed to several factors including the migrating nature of disadvantaged populations [42], the lack of systematic data collection and follow-up, and the COVID-19 pandemic which significantly shifted the priority agenda for many researchers. In addition to that, many studies focus on testing specific interventions that aim to improve maternal heath [43,44], skipping as such the important examination of baseline data and maternal health status of the targeted population.…”
Section: Status Of Maternal Health Among Disadvantaged Populations In...mentioning
confidence: 99%
“…This strain was already evident due to limited capacities, shortage in skilled health professionals, as well as limited supply of medications and equipment [ 14 16 ]. Additionally, it has been revealed that women's health, among other critical healthcare concerns, represents a central concern for refugees in Lebanon, further underscoring the complexities faced by the healthcare system [ 17 ].…”
Section: Introductionmentioning
confidence: 99%